ANALISIS IKLAN SYNOPSIS IKLAN TOKOPEDIA VERSI “PASRAH” 2015 - Sitti Maesurah (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2019)
AbstractAdvertising is one of the most important things in supporting the success of the goods or services offered to the public. Television advertisements are one of the advertisements that are often seen by the public because of the excess audio visual effects. In modern society, there are hardly any people who are not preoccupied with advertising activities. This can help us to realize and understand how important it is to have an institution or institution that integrates all the components and mechanics involved in advertising. Because, advertising is used by everyone, not only by the users of consumer goods, but in essence related to the mass information system in the political, economic, social, cultural and technological fields. Each other interacts using the information system referred to and spread all the problems associated with the system, including religious issues. From this description, what synopsis of Tokopedia "Resign" ads will be explored. This research shows that Tokopedia advertisement is considered not effective enough to convey a message even though this advertisement is quite entertaining for some people. But the message conveyed was blurred because so many meanings could be created from the short 30 second ad. But at least this advertisement can still fulfill the function as brand awareness. Keywords: Advertising, Synopsis, Marketing, Marketing Communication.